1996
DOI: 10.1111/j.1476-5381.1996.tb15734.x
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic GMP‐independent effects of nitric oxide on guinea‐pig uterine contractility

Abstract: 1 The role of nitric oxide (NO) in the regulation of uterine contractility has yet to be clearly defined. We evaluated the effect of NO (in the form of S-nitroso-L-cysteine, CysNO) upon uterine contractility and guanosine 3',5'-cyclic monophosphate (cyclic GMP) accumulation in pregnant and nonpregnant guinea-pig myometrium.2 While CysNO had no effect upon spontaneous contractile activity in either pregnant or nonpregnant uterine tissues, addition of CysNO resulted in an immediate and reversible relaxation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0
1

Year Published

1998
1998
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 30 publications
2
34
0
1
Order By: Relevance
“…We have examined the heretical notion that relaxation of the myometrium by NO is independent of cGMP elevation as a result of soluble guanylyl cyclase. Although this notion was initially rejected by many on the basis that the dogma established by the 1998 Nobel for Physiology or Medicine [25] demanded that NO signals through cGMP in smooth muscle, it is now clearly established from our work and that of others that NO-mediated relaxation of uterine muscle is independent of global cGMP elevation no matter whether this is studied in animal [26] , primate [27] or human [28] . Cyclic GMP is not without effect however.…”
Section: No-mediated Relaxationmentioning
confidence: 89%
“…We have examined the heretical notion that relaxation of the myometrium by NO is independent of cGMP elevation as a result of soluble guanylyl cyclase. Although this notion was initially rejected by many on the basis that the dogma established by the 1998 Nobel for Physiology or Medicine [25] demanded that NO signals through cGMP in smooth muscle, it is now clearly established from our work and that of others that NO-mediated relaxation of uterine muscle is independent of global cGMP elevation no matter whether this is studied in animal [26] , primate [27] or human [28] . Cyclic GMP is not without effect however.…”
Section: No-mediated Relaxationmentioning
confidence: 89%
“…There are conflicting reports in the literature concerning its role in the regulation of myometrial contractility. Functional studies in the rat and guinea pig reported that the myometrium is relatively insensitive to cGMP (5,7,15), especially in comparison to vascular smooth muscle (16). The other study, in contrast, demonstrated that cGMP can modulate myometrial contractile activity (8).…”
Section: Discussionmentioning
confidence: 85%
“…These studies offered evidence consistent with current dogma, that the effect of NO on uterine smooth muscle relaxation occurs via elevations in cGMP and concluded that an NO-GC relaxation pathway exists in the uterine smooth muscle. However, the other study (5) reported that NO can indeed alter agonist-evoked uterine contractility, but the effect of NO does not require the activation of cGMP. The novel NO-independent type of sGC activator YC-1 has attracted much attention recently because of its unique action profile.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The IC 50 for the transnitrosylating agent cysteine-NO to relax human myometrium in tissue bath experiments is approximately 1 M (Buxton et al, 2001). Elevations in cGMP that accompany NO stimulation can be prevented by pretreatment of tissues with inhibitors of soluble guanylyl cyclase such as 1H- [1,2,4]oxadiazolo [4,3-a]quinoxalin-1-one (Buxton et al, 2001), 6-anilino-5,8-quinolinedione (LY 83583), (Kuenzli et al, 1998), or 3,7-bis(dimethylamino) phenothiazin-5-ium (methylene blue), (Kuenzli et al, 1996). Stimulation of 1H- [1,2,4]oxadiazolo [4,3-a]quinoxalin-1-one-treated myometrial tissues with NO donors results in relaxation without cGMP elevation.…”
Section: Introductionmentioning
confidence: 99%